Isolation from Blood Platelets and Polymorphs of A Ca2+-Dependent Regulator Protein [CDR] which Activates Cyclic Nucleotide Phosphodiesterase - Young, N. J.; Crawford, N. (Thrombosis and Haemostasis, 1979)
In recent years a low molecular weight (15-20,000) heat stable, calcium binding protein [CDR, or modulator protein] has been identlfied and isolated from a wide variety of tissues (heart, brain, testis, gizzard, red cells and platelets). This protein has been shown to have a multi-functional role in controlling the activities of cyclic nucleotide phosphodiesterase, adenylate cyclase, muscle protein kinase, Ca2+Mg2+ ATPase and also the phosphorylation of membrane proteins and assembly-disassembly of microtubules. We have isolated a similar protein from human platelets and guinea pig PMN leucocytes by solubilisation of the cells in urea and precipitation with methanol followed by DE 52 cellulose and G100 Sepharose chromatography. Both the isolated proteins purified to homogeneity have molecular weights on dodecyl sulphate/polyacrylamide gel electrophoresis of 16-17000 and they comigrate with the CDR protein similarly isolated from bovine brain. Tested against activator-deficient brain cyclic nucleotide phosphodiesterase the platelet protein showed a Ca2+-dependent 4 fold enhancement of activity comparable to that shown by polymorph CDR [4 fold] but less than that achieved with bovine brain CDR [5-9 fold]. A number of other physico-chemical properties of the three regulatory proteins have been compared.